Study of Tree Diversity and Biomass in Natural and Managed Site of Ridge Forest Ecosystem, Delhi Forest, India - Ekta; Baishya, Ratul; Hasan, Aftab (Indian Forester, 2022)
Tree diversity and biomass (above and below-ground) were studied in natural and managed sites of Delhi Ridge Forest. The study was conducted in the Northern Ridge (NR) and South-Central Ridge (SCR) of the forest ecosystems. In the natural site of both the ridges, Prosopis juliflora (IVI= 105) was the dominant species due to its invasive nature. Eucalyptus tereticornis (IVI =41.7) and Pongamia pinnata (IVI= 63.5) was were dominant species in the managed site of NR and SCR, respectively. Rare species in the natural site was Wrightia tinctoria. In managed site, Thuja orientalis (IVI=4.08) and Ficus bengalensis (IVI= 4.6) were rare. The maximum biomass was found in aboveground biomass of the natural site of Delhi NR forest i.e. aboveground biomass (AGB) ranged was from 44.59 Mg ha-1 to 89.99 Mg ha-1 while the belowground biomass (BGB) was 17.29 ranged from 9.16 Mg ha-1 to 17.29 Mg ha-1. The least AGB was in the managed site of SCR (44.59 Mg ha-1). The total biomass of the NR ranged between 70.35 to 107.28 Mg ha-1. In SCR, it ranged between 53.75 to 96.22 Mg ha-1 which was low as compared to NR due to high human disturbance and poor soil quality. AGB and tree density was found to be maximum in 10-30 cm diameter class in all the sites of Ridge Forest. Prosopis juliflora was the most important tree species in ridge ecosystem as it allocated approximately 50% of the total biomass. Trees of Delhi ridge forest falls under lower diameter classes due to disturbance regime. Variations in species composition, density, diameter distributionpattern, biomass and Carbon stock in the Northern and South-Central Ridge were attributed to two different forest management practices adopted. Hence, both the Ridge Forest had potential for carbon sequestration due to presence of large number of trees belonging to small dbh classes.